The Role of Glucoseamine Sulfate on Osteoarthritis: An update - Hasan, Md Rashidul; Ahasan, HAM Nazmul; Chowdhury, Md Faizul Islam; Rahman, M Matiur (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3329/jom.v7i1.1359 J MEDICINE 2006; 7 : 32-35